FGF23 and Cause‐Specific Mortality in Community‐Living Individuals—The Health, Aging, and Body Composition Study. Issue 3 (10th November 2020) - Sharma, Shilpa; Katz, Ronit; Dubin, Ruth F.; Drew, David A.; Gutierrez, Orlando M.; Shlipak, Michael G.; Sarnak, Mark J.; Ix, Joachim H.
Abstract : Objectives: Fibroblast growth factor (FGF)‐23 is a key regulator of mineral metabolism and has been linked with left ventricular hypertrophy in animal models. Most existing epidemiologic studies evaluated a C‐terminal FGF23 assay which measures both the intact (active) hormone and inactive fragments. The relationship of intact FGF23 with cause‐specific mortality is unknown. Design: Prospective analyses of data from Health, Aging, & Body Composition (HABC) study. Setting: Community‐living adults aged 70 to 79 years with longitudinal follow up.